2013
DOI: 10.1097/inf.0b013e3182a11526
|View full text |Cite
|
Sign up to set email alerts
|

Health Needs of Refugee Children Younger Than 5 Years Arriving in New Zealand

Abstract: Screening identified health needs in otherwise asymptomatic newly arriving refugee children. A proportion of children required access to multiple specialized medical services and may benefit from a comprehensive pediatric service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
1
22
1
6
Order By: Relevance
“…Nevertheless, it is worth mentioning that we were able to perform and subsequently confirm latent tuberculosis infection by QuantiFERON-TB test only in two out of our eight cases (2 children from Congo). The incidence of latent TB among our study participants is much lower than that reported in previous studies concerning migrant children performed in the United States, New Zealand or Australia with the lowest rate (15%) described among refugee children under 5 years of age arriving in New Zealand [9, 31–33]. It is evident that comparison of the above data may be misleading considering that the countries of origin of the migrants are dissimilar to ours and that these studies were conducted at earlier periods.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Nevertheless, it is worth mentioning that we were able to perform and subsequently confirm latent tuberculosis infection by QuantiFERON-TB test only in two out of our eight cases (2 children from Congo). The incidence of latent TB among our study participants is much lower than that reported in previous studies concerning migrant children performed in the United States, New Zealand or Australia with the lowest rate (15%) described among refugee children under 5 years of age arriving in New Zealand [9, 31–33]. It is evident that comparison of the above data may be misleading considering that the countries of origin of the migrants are dissimilar to ours and that these studies were conducted at earlier periods.…”
Section: Discussioncontrasting
confidence: 62%
“…Oral health is a common area of unmet need among migrant children [23, 24]. Additional clinical problems, including skin, respiratory and surgical conditions have been described frequently by previous investigators, especially among newly arriving refugee children [9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Migrant and refugee children are noted to be particularly at risk of VPDs as many have incomplete or unknown immunisation status and few have serological immunity against some VPDs. 13,14 Arriving migrants may be under-immunised due to multiple factors, such as coming from resource poor countries with suboptimal immunisation coverage and facing interruptions of routine vaccinations while migrating. 11 Post-arrival, migrants may experience barriers with receiving immunisations attributed to socio-cultural differences, difficulties accessing health services, economic troubles, limited language proficiency and health literacy, and/or inadequate medical information and advice.…”
Section: Introductionmentioning
confidence: 99%